Measurement of video initial buffer size for mobile network - Guang CHENG; Min FANG; Hua WU (Tongxin xuebao)
To resolve the difficulty in accurately measure the length of video initial buffering queue,two video platforms,non-encrypted Youku and encrypted YouTube,were selected to research,and the video initial buffer queue length measurement method was proposed.By identifying and analyzing the characteristics of video traffic,correlating the traffic behavior with the playing state,constructing video fingerprint database,accurate measurement of queue length was realized.The experimental results show that the measurement results of the two types could be accurate to the frame,fully meeting the need to accurately evaluate the quality of the video experience.